‘Amalu al-Jumlah al-Ismmiyyah bi Anna Maṣdariyyah fī Riwāyah Abwābu al-Madīnah li Ilyās Khūri: Taḥlīl Naḥwī - Sa'adah, Riyadhus (Middle Eastern Culture & Religion Issues, 2022)
This study aimed to reveal the functions of the jumlah ismiyyah which consist anna al-maṣdariyyah in the novel Abwābu al-Madīnati by Ilyās Khūrī by utilizing syntactic theory related to functions. The data in this study were in the form of jumlah ismiyyah consisting of anna al-maṣdariyyah. Technique of collecting data in this study used the referral method with tapping technique as a basic technique and note-taking technique as an advanced technique. This study used the agih method as the analysis stage with the Direct Element Technique (BUL) as a basic technique with i‘rāb model and substitution technique as an advanced technique. Furthermore, the presentation of the results of data analysis was done by using informal methods. Based on the research that has been done, it can be concluded that in the Abwābu al-Madīnati novel by Ilyās Khūrī, there were 101 jumlah ismiyyah consisting of anna al-maṣdariyyah. Those 101 jumlah ismiyyah were classified based on their functions, such as khabar mubtada`, fā‘il, maf‘ūl bih, mustaṡnā, ma‘ṭūf, and ism majrūr. Jumlah ismiyyah consisting of anna al-maṣdariyyah with the form maṣdar mu`awwal can be replaced with ism in the form of maṣdar ṣarīḥ. The substitution of maṣdar mu`awwal with the form maṣdar ṣarīḥ did not cause a change in meaning and grammatical function because both of them get the same position in a sentence. Then the use of maṣdar mu`awwal in that novel gives a specific time marker for an action in a sentence and makes the meaning of the sentence become more cultured.